Explaining implementation behaviour of the National Incident Management System (NIMS). Issue 2 (28th November 2014) - Jensen, Jessica; Youngs, George
<x xml:space="preserve">Abstract</x> This paper explains the perceived implementation behaviour of counties in the United States with respect to the National Incident Management System (NIMS). The system represents a massive and historic policy mandate designed to restructure, standardise and thereby unify the efforts of a wide variety of emergency management entities. Specifically, this study examined variables identified in the NIMS and policy literature that might influence the behavioural intentions and actual behaviour of counties. It found that three key factors limit or promote how counties intend to implement NIMS and how they actually implement the system: policy characteristics related to NIMS, implementer views and a measure of local capacity. One additional variable—inter‐organisational characteristics—was found to influence only actual behaviour. This study's findings suggest that the purpose underlying NIMS may not be fulfilled and confirm what disaster research has long suggested: the potential for standardisation in emergency management is limited.